BOSHLANG‘ICH SINFLARDA ERTAK JANRINI O‘QITISHDA INNOVATSION METODLARDAN FOYDALANISH - Jamolova Mohigul Baxtiyorovna; Bakhtiorova Sabrina Bobirovna (Innovate Conferences, 2025)
This article reveals the importance of using innovative methods in teaching fairy tales in primary grades, and the article provides practical examples, through which it is shown the possibilities of making fairy tale teaching more effective for primary school students.
Keywords: education, interactive method, innovative, teacher, spirituality, genre, value, fairy tale, legend